Commonly reported gynecological morbidities and health-seeking behaviours among reproductive age women in urban Nigeria (1998)
The present study investigated the commonly reported gynecological morbidities by reproductive age women in some/urban areas of south western Nigeria. Specifically the study attempted to determine the proportion of the reproductive age women surveyed reported the symptoms associated with obstetrics and gynecological morbidity, the perceived causes of such obstetrics and gynecological morbidity in the women, whether such women sought treatment or consultation for specific symptoms, and in what kind of health facilities., The Ex post facto research design was adopted in the study. The subjects used for the study were randomly selected from four health facilities located in the Ibadan metropolis, south western Nigeria. The findings from the study revealed that 91% of the respondents have had cause to report their problem to either government hospital, primary health center, private hospital, a sub-center or traditional hospital. Also, 55% of the respondents had their medium of information about health programmes through the radio, while the remaining 45% had been adequately informed about health programmes through the other media like television, magazines, workshops or seminars. About 80% claimed that they had menstrual disorders of heavy or light irregular bleeding, painful menstruation or spotting between periods, while79.6% claimed to have anaemia indicated by feeling excessively weak, tired or breathless during household activities. Some 60.4% of the respondents claimed to have lower reproductive tract infections while 30.7% stated that they have acute pelvic inflammatory disease, which is the lower abdomen pain or vagina discharge with fever. Also, about 58.4% was the percentage of women who sought or consultation for specific symptoms in the private hospital while the rest used the network of health centers and sub-centers available in their areas under the primary health care system. The implication of this findings were highlighted and discussed